Forensic and Pharmaceutical Risks in the Organization of Pharmacotherapy of Covid, Post-Covid and Long-Covid Disorders. COVID-19 and Vaccination Practice Standards. - Shapovalova, Viktoriia (SSP Modern Pharmacy and Medicine, 2022)
The COVID-19 pandemic has strained the healthcare system. It is important to consider forensic and pharmaceutical risks in the organization of vaccination practices and pharmacotherapy of covid, post-covid and long-covid disorders. Scientific sources on the clinical characteristics of SARS-CoV-2, COVID-19 have been systematized. The standards of vaccination practice (immunization, vaccination) of different age categories of the population in Ukraine, England, USA, Belgium, Greece, Japan, and Portugal were analyzed. Proven that the organization of pharmacotherapy schemes is difficult due to the presence of mixed infections, comorbid and complicated forms of diseases, the formation of virus resistance to drugs, and the development of secondary immunological insufficiency. The risks of pharmacotherapy with regard to mortality in patients with COVID-19 due to the development of severe lung lesions and systemic multiorgan pathology are indicated. Schemes of combined pharmacotherapy including antiviral, anti-inflammatory drugs, glucocorticosteroids, genetically engineered biological drugs and "targeted" basic anti-inflammatory drugs were analyzed. The theoretical prerequisites for "repositioning" (drug repurposing) for the treatment of COVID-19 and ego complications are indicated. New directions of anti-inflammatory pharmacotherapy of COVID-19 Janus kinase with a range of anti-inflammatory and antiviral effects were noted. Emphasis was placed on the importance of informing health care professionals about forensic pharmaceutical risks in pharmacotherapy and vaccination practices. The relevance of legal support for medical activity in the conditions of a pandemic was noted. Further research is ongoing.